AB0703 Prevalence and Risk Factors of Spondyloarthritis Associated with Inflammatory Bowel Disease in Japanese Patients: A Single Center, Cross Sectional Study. (10th June 2014) - Kamo, K.; Suekane, H.; Shuto, T.; Haraguchi, A.
Abstract : Background: Spondyloarthritis (SpA) is one of the most common extraintestinal manifestations in those patients 1 . In Japanese multicenter study, the musculoskeletal complication of IBD was reported to be 5.8% 2, which is much lower than the global average. On the other hand, many Japanese physicians feel that musculoskeletal symptoms are more frequently present in patients with IBD. In Japan, the prevalence of SpA-IBD is not clear. One reason is that many patients have not been evaluated by rheumatologists. It is possible that a substantial number of patients with IBD have not been recognized to have SpA. Objectives: We aimed to clarify the prevalence and risk factors of IBD associated SpA in Japanese IBD patients. Methods: We performed questionnaire survey about SpA symptoms in 51 patients with Crohn's disease and 93 patients with ulcerative colitis (UC) on their office visit. A consultant rheumatologist (KK) examined the patients who were suspected to have SpA, and classified them based on the Assessment of SpondyloArthritis international Society classification (ASAS) criteria 3 . Results: After the survey by the questionnaire, 46 (33.6%) patients were suspected to have SpA. Twenty (13.9%) patients have SpA: 2 (1.4%) patients were diagnosed as axial SpA and 18 (12.5%) patients were diagnosed as peripheral SpA. The mean disease duration were 12.3 years in the patients with SpA (SpA group) and 9.2 years those without SpA (non-SpA group) (p<0.05). However the age of onset, sex and type of IBD were not significantly different between the groups. The stratified analysis showed in the male patients UC was independently associated with SpA (OR 0.06, 95% CI 0.003 to 0.917, p=0.043) and longer disease duration in the patients with UC was associated with SpA (OR 1.24, 95% CI 1.02 to 1.5, p=0.031). Conclusions: The prevalence of IBD-SpA in Japanese patients (13.9%) may be higher than previously estimated. The correct recognition of SpA will lead to appropriate treatments and further to improvement in ADL and QOL in patients with IBD-SpA. References: Levine JS, Burakoff R. Extraintestinal manifestations of inflammatory bowel disease. Gastroenterol hepatol. 7(4): 235-41, 2011 Sakurai T, Matsui T, K Aoyagi, et al. Extraintestinal complication of inflammatory bowel disease. Stomach and Intestine. 48(5): 591-600, 2013 Rudwaleit, M., Van Der Heijde, D., Landewé, R., Akkoc, N., Brandt, J., Chou, C. T., Dougados, M., et al. The Assessment of SpondyloArthritis International Society classification criteria for peripheral spondyloarthritis and for spondyloarthritis in general. Annals of the Rheumatic Diseases, 70(1), 25–31, 2011 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1050